The connexin 43 carboxyl terminal mimetic peptide αCT1 prompts differentiation of a collagen scar matrix in humans resembling unwounded skin. Issue 8 (10th July 2021) - Montgomery, Jade; Richardson, William J.; Marsh, Spencer; Rhett, J. Matthew; Bustos, Francis; Degen, Katherine; Ghatnekar, Gautam S.; Grek, Christina L.; Jourdan, L. Jane; Holmes, Jeffrey W.; Gourdie, Robert G.
Abstract: Phase II clinical trials have reported that acute treatment of surgical skin wounds with the therapeutic peptide alpha Connexin Carboxy‐Terminus 1 (αCT1) improves cutaneous scar appearance by 47% 9‐month postsurgery. While Cx43 and ZO‐1 have been identified as molecular targets of αCT1, the mode‐of‐action of the peptide in scar mitigation at cellular and tissue levels remains to be further characterized. Scar histoarchitecture in αCT1 and vehicle‐control treated skin wounds within the same patient were compared using biopsies from a Phase I clinical trial at 29‐day postwounding. The sole effect on scar structure of a range of epidermal and dermal variables examined was that αCT1‐treated scars had less alignment of collagen fibers relative to control wounds—a characteristic that resembles unwounded skin. The with‐in subject effect of αCT1 on scar collagen order observed in Phase I testing in humans was recapitulated in Sprague–Dawley rats and the IAF hairless guinea pig. Transient increase in histologic collagen density in response to αCT1 was also observed in both animal models. Mouse NIH 3T3 fibroblasts and primary human dermal fibroblasts treated with αCT1 in vitro showed more rapid closure in scratch wound assays, with individual cells showing decreased directionality in movement. An agent‐based computational model parameterized with fibroblast motility data predicted collagen alignments in simulated scars consistent with that observed experimentally in human and the animal models. In conclusion, αCT1 prompts decreased directionality of fibroblast movement and the generation of a 3D collagen matrix postwounding that is similar to unwounded skin—changes that correlate with long‐term improvement in scar appearance.